HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL DENGAN ORIENTASI RELIGIUSITAS SISWA DI MADRASAH ALIYAH PONPES AL-MUTHMAINNAH SUMBAWA - Lutfi Rajesa; Lukmanul Hakim; Kartika Mustafa (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
This study aims to determine how is the correlation between communication interpersonal and the orientation of religiosity of the students of madrasah aliyah in the pesantren Al-Muthmainnah Sumbawa. This research uses quantitative approach. The research subjects were taken using population study where the subject of the research be taken from the overall population with 142 students of Madrasah Aliyah in the pesantren Al-Muthmainnah Sumbawa. The result of this research shows that there is a correlation between communication interpersonal and the orientation of religiosity with correlation coefficient value (rxy) of 0,687 with p value = 0.0000 / p < 0.05. Based on the average calculation in general, the general picture of communication interpersonal and the orientation of religiosity of the students of madrasah aliyah in the pesantren Al-Muthmainnah Sumbawa is in high category. Based on the calculation for the data obtained from communication interpersonal scale, from 142 subjects, 101 subjects (71 %) are in high category, and 41 subjects (29%) are in moderate category. Meanwhile, from the result of calculation for data obtained from the orientation of religiosity scale, from 142 subjects, 138 subjects (97%) are in high category, and 4 subjects (3%) are in moderate category.